Physiological and Biomechancical Qualities of Young Players in the "EBA" League - A. Vaquera; J.A. Rodríguez; J.G. Villa; J. García; C. Ávila (Asociación Española de Ciencias del Deporte, 2010)
The objective of this study is identify the functional characteristics and mechanics in the jump of young basketball players of EBA League. The findings of the study will allow adaptation of methods and means of training to reach high performance levels. In 10 basketball players aged 19.3±0.7 years aerobic and anaerobic potential, corporal composition and characteristics of the mechanics of jumps were determined in both laboratory and field tests. The players had a weight of 86.8±2.6 and a height of 197.1±2.9 cm, with an average of 8.2±0.3% of body fat, and an average of 50.3±0.5% muscle mass. In the incremental treatmill test they reached a VO2 max of 61.2±1.3 ml.kg-1.min-1; similar to the result obtained in the Course Navette (60.04±1.2 ml.kg-1.min-1) and different in the Cooper test (56.9±1.7 ml.kg-1.min-1). In the battery of jumps on the contact platform the results were: (Abalakov= 41.5±1.4 cm, SJ= 32.1±1.4 cm, CMJ= 35±1.2 cm, RJ30= 42.4±0.8 jumps with a average power of 36.9±2.2 kg/ w, and in the Wingate test they carried out a average power of 594.6±20.2 W (6.85 w/ kg), a peak power output of 693.4±24.6 W (7.98 w/ kg), and an index of fatigue of-28.7. The valuation of these characteristics is supposed to be an instrument to prescribe more individualized training sessions, in order to obtain a higher performance. KEY WORDS: Basketball, Physiology, Aerobic capacity, Anaerobic capacity; Muscular composition, VO2max, Wingate.